Development and initial validation of a measure of cross-lingual practice among mental health practitioners. (17th February 2023) - Garcia de Blakeley, Marta; Stuart, Jaimee; Sheeran, Nicola
Abstract : Objective: Despite the importance of spoken language in psychotherapy processes with clients whose native language is distinct from the language of therapy, there is a dearth of research on mental health practitioners (MHPs) language competence. This research aimed to develop the Perceptions of Cross-lingual Practice (PCLP) scale designed to aid MHPs' cross-lingual practice. Method: Study 1 developed items and collected data from Australian MHPs (n = 155) to test the scale's factor structure through exploratory factor analysis. Study 2 (n = 257) confirmed the emergent factor structure of the scale through confirmatory factor analysis and further assessed its reliability and convergent validity. Results: The final 23-item measure had good reliability and validity. Three factors emerged; MHPs' perceptions of self-competence, MHPs' perceptions of difficulties faced by clients, and MHPs' perceptions of barriers for themselves imposed by language. The perceptions of self-competence subscale was weakly related to the other subscales highlighting a disconnect between MHPs' self-perceptions and perceptions of contextual factors. Conclusion: The PCLP is a reliable and valid measure of MHPs' perceptions of cross-lingual practice composed of three subscales each with good psychometric properties that can be used for various purposes in the evaluation and development of MHPs in post-graduate and professional settings.